2001
DOI: 10.1007/s00204-001-0292-8
|View full text |Cite
|
Sign up to set email alerts
|

A repeated 28-day oral dose toxicity study of 17α-methyltestosterone in rats, based on the 'Enhanced OECD Test Guideline 407' for screening the endocrine-disrupting chemicals

Abstract: As part of the international validation project to establish the Enhanced OECD Test Guideline 407, we performed a 28-day repeated-dose toxicity study of 17alpha-methyltestosterone, an exogenous androgen agonist. Special attention was paid to the sensitivity of additional parameters for detecting endocrine-related effects of endocrine-disrupting chemicals, based on the existing Test Guideline 407. Seven-week-old Crj:CD(SD)IGS rats were allocated to one of four groups, each consisting of ten males and ten female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The incidences of the lesions were very low, but were nevertheless judged to be genistein-induced. Histopathological changes in the vagina observed using the same protocol with methoxychlor included severe thickening of mucosal epithelium with mucinification (Okazaki et al 2001), and were also seen with 17a-methyltestosterone (Okazaki et al 2002) and ethinylestradiol (Andrews et al 2002;Yamasaki et al 2002), greatly resembling those generated by 17b-estradiol administered in the diet for 90 days in rats (Biegel et al 1998). The lesions of the vagina in the present study might represent early or very slight effects within the range in the above studies.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The incidences of the lesions were very low, but were nevertheless judged to be genistein-induced. Histopathological changes in the vagina observed using the same protocol with methoxychlor included severe thickening of mucosal epithelium with mucinification (Okazaki et al 2001), and were also seen with 17a-methyltestosterone (Okazaki et al 2002) and ethinylestradiol (Andrews et al 2002;Yamasaki et al 2002), greatly resembling those generated by 17b-estradiol administered in the diet for 90 days in rats (Biegel et al 1998). The lesions of the vagina in the present study might represent early or very slight effects within the range in the above studies.…”
Section: Discussionmentioning
confidence: 49%
“…These reports suggest that our test system, the 28-day oral toxicity study based on the existing TG 407, with intact adult rats might have lower sensitivity than assays on ovariectomized or immature animals. Our previous studies revealed that assessment of histopathological features, the weights of endocrine-linked organs, serum hormone levels and the estrous cycle allow detection of endocrine-related effects with flutamide (Toyoda et al 2000), 17a-methyltestosterone (Okazaki et al 2002) and methoxychlor (Okazaki et al 2001), all these being relatively strong agonists or antagonists. However, in the case of a weak agonist or antagonist like genistein, it might be difficult to obtain unequivocal data with our test system alone and results of other tests such as uterotrophic assays, Hershberger assays and in vitro assays might be needed to identify any endocrine-related effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential value of this enhanced protocol is presently being investigated in a worldwide effort by 13 laboratories using 10 chemicals known to interact with the endocrine system through different mechanisms (Andrews et al 2001(Andrews et al , 2002Okazaki et al 2001Okazaki et al , 2002aOkazaki et al , 2002bToyoda et al 2000;Yamasaki et al 2002aYamasaki et al , 2002b. Our laboratory was assigned to conduct a study with a strong antiestrogen (tamoxifen).…”
mentioning
confidence: 98%
“…Presence of dose-related pattern, visually Nishiguchi et al, 1997;Nishiguchi et al, 1994;Takagi et al, 1992b;Nakano et al, 1992;Tamura et al, 1983;Yamazaki et al, 2005;Chemical product Safety Center, et al, 2007;Topping et al, 2007;Guijie et al, 2006;Poon et al, 1998;McClain et al, 2006;Sato et al, 2007;Hellwig et al, 1993;Webb et al, 1993;Mellert et al, 2002;Bär et al, 1995;Arterburn et al, 2000;Goldsmith, 2000;Lee et al, 2004;Janssen et al, 2000;Kanki et al, 2003;O'Hagan and Menzel, 2003;Nakamura et al, 2001;Thomas et al, 1991;Abdo et al, 1986;Morgan et al, 1989;Dunnick et al, 1987;Okazaki et al, 2002;Okazaki et al, 1993;Kato et al, 1993;Jeong et al, 2006;Shim et al, 2003 No change in a related parameter Inui et al, 1997;Takeuchi et al, 1985;Jonker et al, 1993;MacKenzie et al, 1992a;Barber and Topping, 1995;Oshima et al, 1999;Suzuki et al, 1997;Graça et al, 2007;Shimpo et al, 1990 High or low value of control group Inui et al, 1997;…”
Section: -Day Repeated Dosing Study In Accordance With the Chemicalmentioning
confidence: 99%